Delusions Content in the Algerian Schizophrenic Inpatients- A Clinical psychoanalytic Study: Case Study in the Psychiatry Hospital of Tiaret - Bouzouina , Ahmed; Amar, Abd Elhak (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study aims at identifying the content of delusions within persons diagnosed by mental physician being schizophrenic based on the nature, the type, and the motives in the light of the two main perspectives the Freudian theory on psychosis and the Lacanian Theory on psychosis. The Content Analysis method has been adopted to analyse in depth the collected data through utilizing a designed questionnaire by the research conductor targeting at collecting delusions from patients hospitalized in the district psychiatry. The study focused on a purposive sample of three participants inserted since a time in the psychiatric hospital in the area of Tiaret. The Study reveals that there exist delusions in the psychotic discourse although being medicated with anti-psychotic medicines. The study also resulted in an agreement with Sigmund’s Freud vision to the type, nature, and origin of delusions which is the quality of the Mother-Infant Relationship which shows a clear pathology in the discourse of the three cases, as well as Jacques Lacan’s perspective which, but, thumbs the concept of the Name-of-the Father; this latter reveals that the father is either absent or he has been absented in the triad relationship: Mother-Infant-Father demonstrated in the obtained results of the current study.